Competitive Fitness of Oseltamivir-Sensitive and -Resistant Highly Pathogenic H5N1 Influenza Viruses in a Ferret Model - Govorkova, Elena A. (American Society for Microbiology (ASM), 2010)
The fitness of oseltamivir-resistant highly pathogenic H5N1 influenza viruses has important clinical implications. We generated recombinant human A/Vietnam/1203/04 (VN; clade 1) and A/Turkey/15/06 (TK; clade 2.2) influenza viruses containing the H274Y neuraminidase (NA) mutation, which confers resistance to NA inhibitors, and compared the fitness levels of the wild-type (WT) and resistant virus pairs in ferrets. The VN-H274Y and VN-WT viruses replicated to similar titers in the upper respiratory tract (URT) and caused comparable disease signs, and none of the animals survived. On days 1 to 3 postinoculation, disease signs caused by oseltamivir-resistant TK-H274Y virus were milder than those caused by TK-WT virus, and all animals survived. We then studied fitness by using a novel approach. We coinoculated ferrets with different ratios of oseltamivir-resistant and -sensitive H5N1 viruses and measured the proportion of clones in day-6 nasal washes that contained the H274Y NA mutation. Although the proportion of VN-H274Y clones increased consistently, that of TK-H274Y virus decreased. Mutations within NA catalytic (R292K) and framework (E119A/K, I222L, H274L, and N294S) sites or near the NA enzyme active site (V116I, I117T/V, Q136H, K150N, and A250T) emerged spontaneously (without drug pressure) in both pairs of viruses. The NA substitutions I254V and E276A could exert a compensatory effect on the fitness of VN-H274Y and TK-H274Y viruses. NA enzymatic function was reduced in both drug-resistant H5N1 viruses. These results show that the H274Y NA mutation affects the fitness of two H5N1 influenza viruses differently. Our novel method of assessing viral fitness accounts for both virus-host interactions and virus-virus interactions within the host.